Development of audiovisual media on “Mold” material based on guided inquiry to improve students’ critical thinking skills - Rahel Natalia Saragih Munthe; Utami Sri Hastuti; Herawati Susilo (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The needs analysis shows that students must improve their critical thinking skills. The number of students who could differentiate various types of mold conidia based on their structure was also smaller. The purpose of this research and development was to test the effectiveness of audiovisual media on the topic “Mold” based on Guided Inquiry on “Microscope Using Techniques, Description of Colony Morphological Characteristics, and Mold Microscopy” to improve students’ critical thinking skills. This type of research is a quasi-experimental study with the Non-randomized Pretest Posttest Control Group design and follows the stages of the development model from Lee and Owens. Data collection uses validation sheets, response questionnaires, pretest, and posttest questions. Data analysis used the N-Gain score and the Mann Whitney test. The results of the study showed that there was a significant difference between the experimental class which was taught using audiovisual media on the topic “Mold” based on Guided Inquiry, compared to the control class which was taught using conventional Power Point (PPt) media without audiovisual media, so it can be concluded that the media audiovisual on the topic “Mold” is effective in improving students’ critical thinking skills.Abstrak Analisis kebutuhan menunjukkan mahasiswa masih perlu meningkatkan keterampilan berpikir kritis. Jumlah mahasiswa yang mampu membedakan macam-macam konidia kapang berdasarkan strukturnya juga lebih sedikit. Tujuan penelitian dan pengembangan ini adalah untuk menguji keefektifan media audiovisual pada topik “Kapang” berbasis Guided Inquiry tentang “Teknik Penggunaan Mikroskop, Deskripsi Ciri-ciri Morfologi Koloni, dan Mikroskopis Kapang” untuk meningkatkan keterampilan berpikir kritis mahasiswa. Jenis penelitian ini adalah penelitian kuasi eksperimental dengan desain Non-randomized Pretest Posttest Control Group dan mengikuti tahapan model pengembangan dari Lee dan Owens. Pengumpulan data menggunakan lembar validasi, angket respon, soal pretest dan posttest. Analisis data menggunakan N-Gain score dan uji Mann Whitney. Hasil penelitian menunjukkan bahwa ada perbedaan signifikan antara kelas eksperimen yang dibelajarkan dengan menggunakan media audiovisual pada topik “Kapang” berbasis Guided Inquiry, dibandingkan dengan kelas kontrol yang dibelajarkan dengan menggunakan media Power Point (PPt) secara konvensional tanpa media audiovisual, sehingga dapat disimpulkan bahwa media audiovisual pada topik “Kapang” efektif meningkatkan keterampilan berpikir kritis mahasiswa.